Corrosion Performance of (Ha-Psz) Bio Ceramic Coated Ti-20Co Alloy in Simulated Physiological Media - Alrawi, Khalid R; Alzubaydi, Thair L; Alsaaidy, Murtdha A (Al-Nahrain Journal of Science, 2018)
The present investigation provides experimental results of corrosion performance in simulated body fluid of Ti-20Co medical alloy coated with hydroxyapatite (HA) and Partially Stabilized Zirconia (PSZ) composite layer by electrphoretic deposition (EPD) technique. A three mixing ratios of HA and PSZ powders (namely 90%HA+10%PSZ, 66%HA+34%PSZ and 25%HA+75%PSZ) were electrophoretically deposited on the surface of a Ti-20Co substrates. Post heat treatment at 800Co in inert environment was performed to improve the adhesion strength of the coated layers. The coated samples were subjected to electrochemical study in artificial saliva (Modified Carter\'s solution) and simulated blood plasma in order to determine the optimum coating conditions that can give corrosion resistance in simulated body fluid condition. The influence of mixing ratios and deposition thickness on the corrosion performance of the alloy are discussed in details based on the Open Circuit Potential (OCP), corrosion potential and corrosion rate using potentiodynamic polarization. Results showed that the coating efficiency is highly depending on parameters like composition, coating thickness, layer porosity and adhesion to substrate. The corrosion aspects resulting from various deposition thicknesses are discussed in details.